Life course transitions and changes in network ties among younger and older adults. (June 2022) - Weiss, Jordan; Lawton, Leora E.; Fischer, Claude S.
Abstract: Several theories of the life course highlight the importance of social connections and ties for coping with transitions that occur at different ages. Individuals rely on family, friends, and colleagues to adapt to these transitions which may in turn change the composition of their networks. Yet, little is known about the association between life cycle transitions and changes in network characteristics. We used fixed effects regression models with three waves of egocentric network data from the UC Berkeley Social Network Study (UCNets) to examine how career- and family-related life cycle transitions during two key life stages—young adulthood and the transition from middle to old age—are associated with network turnover, the proportion of the network comprised of kin, and confidence in receiving support from personal networks. Younger adults experienced churn following a birth and marriage or partnership, while no life transition was associated with changes in proportion kin, and only with the birth of a child did confidence decline. Among older adults, no transition was associated with any measured event, suggesting that older adults maintain more stable relationships compared to young adults and can weather life events without significant disruptions to their networks.